Implementasi Permanan Playmate Karpet Edukatif Jejak Kaki dan Tangan Dalam Meningkatkan Motorik Kasar Anak Usia Dini 5-6 Tahun - Sipa Lestari; Elnawati Elnawati; Ibnu Hurri (Alahyan Jurnal Pengabdian Masyarakat Multidisiplin, 2025)
This study aims to analyze the implementation of the foot-and-hand educational carpet playmate game in improving early childhood gross motor skills in the age group of 5-6 years. Gross motor skills are abilities that involve the coordination of large muscles such as hands, feet, and the body as a whole, which is very important to support the physical development of children. This research is motivated by the need for fun, interactive, and effective learning strategies to develop early childhood gross motor skills. The research method used is Classroom Action Research with the Kemmis and McTaggart model which consists of planning, action, observation, and reflection. The subject of the study is 5-6 years old children at KB Al Mahmudin, with a total of 20 students. Data was collected through observation, interviews, documentation, and field notes. Data analysis techniques were carried out in a qualitative and quantitative descriptive manner to see the improvement of children's gross motor skills. The results of the study show that the implementation of the foot-and-hand educational carpet playmate game can significantly improve children's gross motor skills. Children showed improvements in aspects of balance, coordination of movements, agility, and muscle strength. The learning process becomes more interesting because this game provides a hands-on experience that involves active physical movements of the child. In addition, teachers and parents responded positively to this method because it was able to create a fun and interactive learning atmosphere. This study concludes that the foot-and-hand educational carpet playmate game is an effective learning medium to improve early childhood gross motor. This study recommends the use of this game in daily learning activities in early childhood education institutions.